The relationship between vitamin K and metabolic dysfunction-associated fatty liver disease among the United States population: National Health and Nutrition Examination Survey 2017–2018 - Wang, Xinyue; Zhang, Wei; Huang, Jiale; Li, Hongwei; Gao, Jian (Frontiers in Nutrition, 2023)
Background: The effect of vitamin K is associated with several pathological processes in fatty liver. However, the association between vitamin K levels and metabolic dysfunction-associated fatty liver disease (MAFLD) remains unclear. Objective: Here, we investigated the relationship between vitamin K intake and MAFLD risk by employing the American National Health and Nutrition Examination Surveys (NHANES) including 3571 participants. Methods: MAFLD was defined as hepatic steatosis with one or more of the following: overweight or obesity, type 2 diabetes; or >2 other metabolic risk abnormalities. The total vitamin K was the sum of dietary and supplement dietary intake. The relationship of between log10(vitamin K) and MAFLD was investigated using survey-weighted logistic regression and stratified analysis, with or without dietary supplementation. Results: The MAFLD population had a lower vitamin K intake than the non-MAFLD population (P=0.024). Vitamin K levels were inversely associated with MAFLD in the fully adjusted model (OR=0.488, 95% CI: 0.302–0.787, P=0.006). Consistent results were seen in the group without dietary supplements (OR=0.373, 95% CI: 0.186–0.751, P=0.009) but not in the group consuming dietary supplements (OR=0.489, 95% CI: 0.238‒1.001, P=0.050). Conclusions: Vitamin K intake may be a protective factor for MAFLD, especially for individual not using dietary supplements. Nevertheless, more high-quality prospective studies are needed to clarify the causal relationship between them.